EFFECT OF PUBLIC DEBT ON THE NIGERIAN ECONOMIC DEVELOPMENT (Journal of the Management Sciences, 2023)
This study is an empirical investigation into the effect of public debt on Nigerian economic development. It was aimed at determining the effects of domestic debt on the human development index and the per capita income of Nigeria and was also aimed at determining the effect of External debt on the human development index and the per capita income of Nigeria. This study was anchored on the classical/traditional theory of public debt. Internal and external debts were used as the independent variables while HDI and PCI served as the dependent variables. Secondary data were sourced from the Central bank of Nigeria’s Statistical bulletin. The Granger causality test was adopted for the empirical analysis. The research revealed that both Public debt and Domestic debt has no significant effect on Per Capita Income and Human Development Index respectively. It was recommended that although public debts are inevitable especially for a developing nation like Nigeria, new debts should be incurred on the basis that most of the amounts should go into viable projects with promising outlook of moving the nation from consumption to production. Also, policymakers in Nigeria should analyze and examine fluctuations in the economy of countries in which they are dependent on to prevent it from having a more adverse effect on the country’s economy.
Keywords: human development index; Debts; per capita income